Editorial - Martí-Vilar, Manuel (2020)
The Digital Journal of Research in University Teaching (RIDU) presents a number dedicated to "Values ​​and professional ethics" in the midst of the health crisis caused by COVID- 19 which has affected many problems, but especially Higher Education. It is an honor to be a guest editor for this fifth RIDU publication assigned to monographic topics relevant to University Education. With this number, RIDU is achieving be an enriching space of knowledge with valuable research within the field educational program with the participation of authors from universities in Mexico, Peru, Chile, Spain, Italy, Costa Rica and Argentina.